2011
DOI: 10.1007/s12640-011-9274-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Glyphosate- and/or Mn/Zn-Ethylene-bis-Dithiocarbamate-Containing Pesticides Leads to Degeneration of γ-Aminobutyric Acid and Dopamine Neurons in Caenorhabditis elegans

Abstract: Previous studies demonstrate a positive correlation between pesticide usage and Parkinson’s disease (PD), which preferentially targets dopaminergic (DAergic) neurons. In order to examine the potential relationship between two common pesticides and specific neurodegeneration, we chronically (24 hours) or acutely (30 min) exposed two Caenorhabditis elegans (C. elegans) strains to varying concentrations (LC25, LC50 or LC75) of TouchDown® (TD) as per cent active ingredient (glyphosate), or Mancozeb® (MZ) as per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 47 publications
3
63
0
Order By: Relevance
“…Oxidative stress also resulted in the neurodegeneration of dopaminergic (DAergic) neurons, indicated by the fact that treated worms showed a significant decrease in DA concentration compared to untreated worms [143]. Similar neurodegeneration has been shown following exposure to mancozeb [144,145].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 65%
See 1 more Smart Citation
“…Oxidative stress also resulted in the neurodegeneration of dopaminergic (DAergic) neurons, indicated by the fact that treated worms showed a significant decrease in DA concentration compared to untreated worms [143]. Similar neurodegeneration has been shown following exposure to mancozeb [144,145].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 65%
“…Manganese-containing dithiocarbamate fungicides, such as maneb and mancozeb, have been researched heavily due to their neurotoxicity [143][144][145]. Manganese exposure by itself has been shown to result in a variety of detrimental effects in C. elegans [146][147][148].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%
“…The synthesis of GABA should then decrease in relation to this intrinsic property of maize-at least when maize becomes the major diet. Moreover, it has been observed that glyphosate itself alters GABA ergic neurons 15 . A maize diet leads to pellagra provoked by niacin deficiency; an associated vitamin B 6 loss should also elicit neurological troubles, dementia or epilepsy, as GABA is a major transmitter in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Its mode of action is to interfere with the synthesis of phenylalanine, tyrosine and tryptophan. There have been a few human case studies possibly linking glyphosate exposure to Parkinsonism, and it has been reported that glyphosate exposure could result in not only dopaminergic but also GABAergic neurodegeneration in C. elegans (Gui et al, 2012;Negga et al, 2011;Negga et al, 2012). In vitro studies have reported glyphosate-induced cell death via apoptosis and autophagy, but glyphosate exposure did not increase alpha-synuclein levels in vitro (Chorfa et al, 2013;Chorfa et al, 2014;Gui et al, 2012).…”
Section: Glyphosatementioning
confidence: 99%